2019
DOI: 10.25186/cs.v14i2.1540
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Land Cover Change and Temperature Analyses: A Study Case in São Paulo State

Abstract: <p>In this research, we combine data analyses with hotspots method to identify the spatio-temporal trend of São Paulo’s coffee cultivation area. Our hypothesis is that coffee cultivation area has been changing significantly in the study area since 1990. Therefore, the main goal of this research was to map the spatial pattern of coffee land use change.  For coffee land use diagnostics, official data of cultivated area, hotspot analyses and growth rate were used. The results demonstrated that coffee cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…This corroborates with Castro et al (2021), which also noted the same concentration. The same was obtained by Coltri et al (2019), which, in the State of Sao Paulo, observed that coffee areas are concentrated in region producing specific coffees, such as "Alta and Média Mogiana" (in English: "High and Low Mogiana").…”
Section: Location and Altimetry Of Coffee-producing Municipalitiessupporting
confidence: 74%
See 2 more Smart Citations
“…This corroborates with Castro et al (2021), which also noted the same concentration. The same was obtained by Coltri et al (2019), which, in the State of Sao Paulo, observed that coffee areas are concentrated in region producing specific coffees, such as "Alta and Média Mogiana" (in English: "High and Low Mogiana").…”
Section: Location and Altimetry Of Coffee-producing Municipalitiessupporting
confidence: 74%
“…Other works add the difficulty of crop recovery after the 1975 frost (Robusti et al, 2017) and the fall in export volume during the economic crisis of (Pereira et al, 2011 as justifications for such change. Likewise, Coltri et al (2019) noted that, in the State of Sao Paulo, between 1990 and 2013, coffee behaved similarly, with municipalities that completely abandoned the coffee crop, as well as a large decrease of planted area in the remaining municipalities. On the other hand, in the State of Minas Gerais, in the region of Triângulo Mineiro and the Alto Paraíba, Moreira et al (2015), noted that between the years of 2008 and 2014, the coffee area had an increase of 23.5% in the mesoregion as a whole.…”
Section: Retraction Of the Coffee Areamentioning
confidence: 91%
See 1 more Smart Citation